Treatment for Nontype 1 Retinopathy of Prematurity by Intravitreal Injection of Antivascular Endothelial Growth Factor Drugs - Haitao Zhang; Xin Yang; Fangfang Zheng; Xiangke Yin; Suhua Wan (Journal of Ophthalmology)
Background. To explore clinical characteristics and treatment reasons for intravitreal injection of antivascular endothelial growth factor (anti-VEGF) drugs in the treatment of nontype 1 retinopathy of prematurity (ROP). Methods. A retrospective study was conducted to screen the nontype 1 ROP from the collected ROP patients who received intravitreal injections of anti-VEGF drugs in Henan Eye Hospital from September 2018 to June 2021. Results. A total of 138 ROP cases (262 eyes) were included in this study, including 39 cases (28.3%), 65 eyes (24.8%) that were the nontype 1 ROP. Compared with the type 1 ROP group, the nontype 1 ROP group had slightly later treatment time (39.8 ± 2.7 weeks vs 38.1 ± 2.6 weeks, P<0.05) and a higher proportion of fusion protein drugs (87.2% vs 54.5%, P<0.05). After intravitreal injection of anti-VEGF drugs, 27 eyes (41.5%) were cured and 38 eyes (58.5%) improved in the nontype 1 ROP group, without recurrence and aggravation cases. There were more lesions in zone II (63 eyes, 96.9%), with stage 2 (40 eyes, 61.5%) and stage 3 (23 eyes, 35.4%), and 58 eyes (89.2%) showed preplus in the nontype 1 ROP group. Treatment reasons included preplus in 58 eyes (89.2%), ridge aggravation in 22 eyes (33.8%), simultaneous treatment of the contralateral eye in 9 eyes (13.8%), no regression of lesions in the persistent stage 2 or 3 over PMA 44 weeks of follow-up in 8 eyes (12.3%), and logistical considerations in 4 eyes (6.2%). Conclusions. Considering some peculiar clinical characteristics, treatment by intravitreal injection of anti-VEGF drugs may be considered carefully for some nontype 1 ROP in critical conditions.